Physical-Chemical Analysis of Water from the Bananeira Arapiraca Alagoas Dam. - Mendonça Cavalcanti, Janesmar Camilo (2022)
It is a fact that universal access to quality water is essential for the health andpreservation of the environment and the consequent sustainability of a society. According toFiocruz (FIOCRUZ, 2020) one in four health care centers in the world lacks basic water services,affecting 2 million people, and more than five million people die each year in the world due towater-borne diseases, according to the WHO UNICEF report. The world follows the increase indeforestation for decades where Cruz (2014) clearly highlights that the goal of improving climateconditions and housing with basic sanitation depends on priorities listed by each country. ThePiauí de Arapiraca river basin suffers intense environmental degradation, receiving in its pathwastewater from homes, industries, health centers and agricultural activities, which flow into thedam of Vila Bananeira, site and object of ongoing research. There are several ways to assess waterquality in water bodies, among them physicochemical analyzes stand out as quality parameters.The National Health Foundation physical-chemical analysis guide was used, whose parameterswere Total Alkalinity, Chlorides, Turbidity, pH, Total Hardness and Conductivity, of water fromthe dam of Vila Bananeira, collected in two months with different rainfall levels. All parameterswere in normal conditions according to the Ministry of Health Ordinance No. 2.914/2011according to national and international standards.